Nature and nurture in early child development - Keating, Daniel P., 1949- (Cambridge, UK : Cambridge University Press, 2011)
'For developmental scientists, the nature versus nurture debate has been settled for some time. Neither nature nor nurture alone provides the answer. It is nature and nurture in concert that shape developmental pathways and outcomes, from health to behavior to competence. This insight has moved far beyond the assertion that both nature and nurture matter, progressing into the fascinating terrain of how they interact over the course of development. In this volume, students, practitioners, policy analysts, and others with a serious interest in human development will learn what is transpiring in this new paradigm from the developmental scientists working at the cutting edge, from neural mechanisms to population studies, and from basic laboratory science to clinical and community interventions. Early childhood development is the critical focus of this volume, because many of the important nature-nurture interactions occur then, with significant influences on lifelong developmental trajectories'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Nature and nurture; Genetic psychology; Child psychology